2008
DOI: 10.1111/j.1365-2567.2007.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an anti‐idiotypic antibody that defines a B‐cell subset(s) producing xenoantibodies in primates

Abstract: Summary Synthetic anti‐idiotypic antibodies represent a potentially valuable tool for the isolation and characterization of B cells that produce xenoantibodies. An anti‐idiotypic antibody that binds to a subset of B cells producing antibodies encoded by the variable‐region heavy chain 3 (VH3) germline genes DP35 [immunoglobulin variable‐region heavy chain 3‐11 (IGHV3‐11)], DP‐53 and DP‐54 plus a small number of VH4 gene‐encoded antibodies in humans has recently been identified. These germline progenitors also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The similarity in the structure of the xenoantibodies that initiate rejection of porcine xenografts provides new opportunities for the design of novel approaches to limit xenoantibody-mediated rejection. Structure-based drug design or the elimination of B cells producing xenoantibodies may be useful as adjunct therapeutics to prolong xenograft survival (45). Specific elimination of anti-gal B cells using alpha-gal linked toxins in mice has been performed without toxicity to the mice and without affecting production of antibodies with other specificities (46).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in the structure of the xenoantibodies that initiate rejection of porcine xenografts provides new opportunities for the design of novel approaches to limit xenoantibody-mediated rejection. Structure-based drug design or the elimination of B cells producing xenoantibodies may be useful as adjunct therapeutics to prolong xenograft survival (45). Specific elimination of anti-gal B cells using alpha-gal linked toxins in mice has been performed without toxicity to the mice and without affecting production of antibodies with other specificities (46).…”
Section: Discussionmentioning
confidence: 99%
“…A study performed by Fischer‐Lougheed et al . in rhesus macaques demonstrated that anti‐Gal secreting cells were CD5 − CD11b + , similar to the B‐1b cells in GalTKO mice . Unfortunately, the same approach, which relies on using the anti‐Gal IgM receptor on antibody‐secreting cells to define xenoantibody‐producing cells, has little applicability in the current era, when the relevant xenoantibodies under study are directed to poorly defined non‐Gal antigens.…”
Section: Antibody Responsesmentioning
confidence: 99%
“…Indeed, depletion of the anti-Gal antibody leads to more favorable outcomes, further implicating B-cells in the rejection of xenotransplants 71 73 . The phenotypic characteristics of anti-Gal antibody-producing subpopulations of B-cells in humans are not clearly identified 72 . One study has shown that splenic B-cells produce anti-Gal antibodies, whereas peritoneal B-cells do not, although they do express anti-Gal receptors 73 .…”
Section: Role Of Cellular Immunity In Xenogeneic Rejectionmentioning
confidence: 99%